2018
DOI: 10.1007/978-3-319-72761-5_86
|View full text |Cite
|
Sign up to set email alerts
|

Creationism and Intelligent Design

Abstract: Until recently, little attention has been paid in the school classroom to creationism and almost none to intelligent design. However, creationism and intelligent design appear to be on the increase and there are indications that there are more countries in which schools are becoming battlegrounds over them. I begin by examining whether creationism and intelligent design are controversial issues, drawing on Robert Dearden's epistemic criterion of the controversial and more recent responses to and defences of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Creationism exists in a number of different versions but, depending on the country, from as few as 5% to over 50% of adults reject the theory of evolution. Instead, they believe that life came into existence as described by a literal (fundamentalist) reading of the early parts of the Bible, the Qu'ran or other scriptures and that the most that evolution has done is to change species into related species (Miller et al, 2006;Reiss, 2018b). For a creationist it is possible, for example, that the various species of hedgehogs (17 are generally identified, classified into five genera) had a common ancestor but this is not the case for the various species of hedgehogs, deer and cats -still less for monkeys and humans, for birds and reptiles or for whales and soft fruit.…”
Section: Evolutionmentioning
confidence: 99%
“…Creationism exists in a number of different versions but, depending on the country, from as few as 5% to over 50% of adults reject the theory of evolution. Instead, they believe that life came into existence as described by a literal (fundamentalist) reading of the early parts of the Bible, the Qu'ran or other scriptures and that the most that evolution has done is to change species into related species (Miller et al, 2006;Reiss, 2018b). For a creationist it is possible, for example, that the various species of hedgehogs (17 are generally identified, classified into five genera) had a common ancestor but this is not the case for the various species of hedgehogs, deer and cats -still less for monkeys and humans, for birds and reptiles or for whales and soft fruit.…”
Section: Evolutionmentioning
confidence: 99%
“…In addition, the share of the population holding creationist beliefs also varies between the states and regions. It has been reported that the acceptance of creationism and intelligent design is on the rise in different countries (Reiss 2018). The level of acceptance of the theory of evolution and its wide range is attributed to different factors, including religious views, cultural traditions, geographical diversity, and individual proficiency (Borgerding and Deniz 2018; Deniz and Borgerding 2018).…”
Section: Introductionmentioning
confidence: 99%